KINERJA ANGKUTAN UMUM PENGUMPAN (FEEDER) LRT KOTA PALEMBANG (STUDI KASUS RUTE STASIUN DJKA – TERMINAL PLAJU) - Zulkarnain, Yules Pramona; Asmawi, Bazar; Alzahri, Syahril; Oktaliani, Triana (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2024)
A feeder system is a transportation system that aims to serve parts of the city that are beyond the reach of the main modes of transportation. The feeder system is designed to be used in residential areas towards the main road corridor so as to create a better hierarchy of public transportation systems between the main mode, branch mode, feeder mode. With the holding of this feeder, one of them is a milestone to increase LRT (Light Rail Transit) occupancy. The purpose of this research is to find out how effective and efficient feeder public transportation is and to find out the characteristics of passengers using feeder services on corridor 5, the analysis method used in this study uses a mixed method between descriptive and quantitative. Based on the results of the analysis that has been done, it is known that the background of different passengers at each observation point and the results of the feeder performance with a vehicle density value of 0.322 vehicles / hour, waiting time of 6 minutes, vehicle frequency of 4 - 5 vehicles / km, speed of 17 km / hour, travel time of 0.8 hours, operational capacity of 11.4%, headway 12 minutes, load factor 96% and utility 230 km in one day of operation.